2019
DOI: 10.1039/c8ob02689k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and spectroscopic studies on the chiral self-aggregation of amphiphilic zinc and copper (l)-prolinate-tetraarylporphyrin derivatives in different aqueous media

Abstract: The chiral self-aggregation of (l)-proline porphyrin derivatives depends on both the nature of the media and the coordinated metal ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…As far as the overall aggregation process is concerned, we recently found an analogous two-step process in the aggregation of related cationic L-proline-porphyrin derivatives in analogous aqueous media (Lorecchio et al, 2014;Caroleo et al, 2019), and also in the study of the interaction of a chiral Zn-porphyrin derivative with chiral anionic surfactants in water, that results in the rapid formation of small sized aggregates, followed by a slower step in which the initial species rearrange in more ordered and specific structures driven by Zn-coordination (Simoncini et al, 2014). Same phenomenon has been also observed by others in organic solvent (Feldborg et al, 2011), in the case of water-soluble tetrapyrrolic macrocycles (El-Hachemi et al, 2016) or, amazingly, even in solid state (Borovkov et al, 2003).…”
Section: Spectroscopic Investigationsmentioning
confidence: 99%
“…As far as the overall aggregation process is concerned, we recently found an analogous two-step process in the aggregation of related cationic L-proline-porphyrin derivatives in analogous aqueous media (Lorecchio et al, 2014;Caroleo et al, 2019), and also in the study of the interaction of a chiral Zn-porphyrin derivative with chiral anionic surfactants in water, that results in the rapid formation of small sized aggregates, followed by a slower step in which the initial species rearrange in more ordered and specific structures driven by Zn-coordination (Simoncini et al, 2014). Same phenomenon has been also observed by others in organic solvent (Feldborg et al, 2011), in the case of water-soluble tetrapyrrolic macrocycles (El-Hachemi et al, 2016) or, amazingly, even in solid state (Borovkov et al, 2003).…”
Section: Spectroscopic Investigationsmentioning
confidence: 99%
“…Very recently, Monti et al reported the possibility of forming chiral suprastructures starting from Zn and Cu cationic ( l )-prolinate-tetraarylporphyrin complexes in different aqueous media (Figure 8a) [42]. As reported by the authors in previous works, the appended-proline group provides the chiral information to read during the aggregation process, and directly determines the chiral features of the formed assemblies, together with other boundary experimental parameters like solvent composition, monomer concentration, charge of the proline unit, and the metal ion coordinated.…”
Section: Solvent-driven Aggregation Protocolmentioning
confidence: 99%
“…For many years, we have focused on the possibility to build up chiral porphyrin suprastructures by assembling inherently chiral porphyrin derivatives having single or multiple stereogenic centers peripherally located on the macrocycle thanks to the conjugation with diverse biomolecules, as amino acids, glucosides or steroids [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. The self-aggregation of these compounds was induced in organic/aqueous mixtures by the so-called “good-bad” solvent protocol, in which porphyrins solubilization in a “good” solvent is followed by the addition of the proper amount of a “bad” one, where typically the macrocycle is insoluble, even at low concentrations.…”
Section: Introductionmentioning
confidence: 99%